Stimulated Nitric Oxide Production and Arginine Deficiency in Cystic Fibrosis Children with Nutritional Failure - Engelen, Mariëlle PKJ (2013)
OBJECTIVE: Reduced nitric oxide (NO) concentrations are found in the airways of many patients with cystic fibrosis (CF) and are associated with increased airflow obstruction. We determined whether upregulated whole body de novo arginine synthesis and protein breakdown are present as a compensatory mechanism to meet the increased demand for arginine and nitric oxide production in pediatric patients with CF and nutritional failure. STUDY DESIGN: In 16 children with CF, studied at the end of antibiotic treatment for a pulmonary exacerbation, and 17 healthy controls, whole body arginine, citrulline, and protein turnover were assessed by stable isotope methodology and de novo arginine synthesis, arginine clearance, NO synthesis, protein synthesis and breakdown, and net protein balance were calculated. The plasma isotopic enrichments and amino acid concentrations were measured by LC-MS/MS. RESULTS: Increased arginine clearance was found in patients with CF (p<0.001) whereas whole body NO production rate and plasma arginine levels were not different. Whole body arginine production (P<0.001), de novo arginine synthesis, and protein breakdown and synthesis (P<0.05) were increased in patients with CF, but net protein balance was comparable. Patients with CF with nutritional failure (n=7) had significantly higher NO production (P<0.05), de novo arginine synthesis, citrulline production (P<0.001), and plasma citrulline concentration (P<0.05) and lower plasma arginine concentration (P<0.05) than those without nutritional failure (n=9). CONCLUSIONS: Nutritional failure in CF is associated with increased NO production. However, upregulation of de novo arginine synthesis and citrulline production was not sufficient to meet the increased arginine needs leading to arginine deficiency.